Hydrodynamics of Steam-Water Two-Phase Flows Through Grooved Walled Passages - Sinitsin Vladimir Vladimirovich; Taranenko Pavel Alexandrovich; Sanaullah Khairuddin; Bassir David; Rigit Andrew Ragai Henry (E3S Web of Conferences)
In this study, we investigated the flow hydrodynamics of mixture of steam and water through a pipe that has grooved walls. The walls were roughened using collars that has circular and squared shapes throughout the inner walls of the flow channel. Our findings indicate that the factors related to the friction of the walls have been associated with wall roughness ranged from 0.6 to 0.63. The velocity deficit near the wall was slightly greater above the smooth walls compared to the rough walls, reflecting the impact of the friction factor. However, the profiles used to quantify the Reynolds normal stresses showed a distinct contrast. In the grooved surface channel, pressure-induced drag dominated, leaving little room for viscous effects and resulting in lower peaks. These stresses were heavily influenced by wall geometry. Notably, in channels with squared grooves, flow profiles were shows a slight decrease compared to those observed over smooth and rough walls.